Effect of the Articular Surface Incongruency on Surgical Outcome of the Distal Radius Fracture. (9th March 2022) - Lee, Chang-Hun; Kwon, Youngmin; Jung, Il Youn; Lee, Bong-Gun; Kim, Sung Jae
Abstract : Purpose . The aim of this study was to demonstrate the joint fragment that mostly affects the outcome of the distal radius fracture surgically treated with a volar locking plate (VLP). Methods . The outcomes of 69 patients with the distal radius fractures were evaluated at their final follow-up. The articular surface was divided into six specific fragments, and computed tomography (CT) was used to evaluate the degree of mismatch of each fragments. A plain radiograph was also obtained for evaluation of the distal radius alignment. Clinical outcomes were measured by using the Disabilities of the Arm, Shoulder and Hand (DASH) and Modified Mayo Wrist Score (MMWS). Univariate analyses were performed, with subsequent multiple logistic regression analyses. Results . The mean follow-up period was 14.8 (range, 12 to 52) months. The group with a worse DASH score showed significantly greater mismatch in the volar and dorsal lunate facets, as well as the central depression of the distal radius (p = 0.042, 0.031, and 0.023, respectively). There was a significant positive correlation between the DASH score and degree of mismatch of the dorsal lunate facet and central depression of the distal radius (p = 0.040 and 0.011, respectively). Groups with worse MMWS showed significantly greater mismatch in the dorsal lunate facet (p = 0.025 ). There was a significant negative correlation between MMWS and abnormal ulnar variance and mismatch of the dorsal lunate facet and central depression of the distal radius (p = 0.041, 0.004, and 0.018, respectively). The result of multiple logistic regression analysis demonstrated that a mismatch of the dorsal lunate facet is a significant predictor for a worse MMWS (odds   ratio = 3.072, p = 0.043 ). Conclusions . Articular surface mismatch of the dorsal lunate facet appears to mostly affect the surgical outcomes of the distal radius fractures using VLP. In cases where the dorsal lunate facet is heavily involved, surgeons should be cautious about its reduction and fixation.